Binding of N-methylscopolamine to the extracellular domain of muscarinic acetylcholine receptors - Jakubík, Jan; Randáková, Alena; Zimčík, Pavel; El-Fakahany, Esam E; Doležal, Vladimír (Scientific reports, 2017)
Interaction of orthosteric ligands with extracellular domain was described at several aminergic G protein-coupled receptors, including muscarinic acetylcholine receptors. The orthosteric antagonists quinuclidinyl benzilate (QNB) and N-methylscopolamine (NMS) bind to the binding pocket of the muscarinic acetylcholine receptor formed by transmembrane α-helices. We show that high concentrations of either QNB or NMS slow down dissociation of their radiolabeled species from all five subtypes of muscarinic acetylcholine receptors, suggesting allosteric binding. The affinity of NMS at the allosteric site is in the micromolar range for all receptor subtypes. Using molecular modelling of the M2 receptor we found that E172 and E175 in the second extracellular loop and N419 in the third extracellular loop are involved in allosteric binding of NMS. Mutation of these amino acids to alanine decreased affinity of NMS for the allosteric binding site confirming results of molecular modelling. The allosteric binding site of NMS overlaps with the binding site of some allosteric, ectopic and bitopic ligands. Understanding of interactions of NMS at the allosteric binding site is essential for correct analysis of binding and action of these ligands.
Keywords: kinetika; sekundární struktura proteinů; Mutant Proteins; křečci praví; ligandy; Protein Binding; receptory muskarinové; zrychlení; N-Methylscopolamine; Molecular Dynamics Simulation; CHO Cells; Tritium; tritium; Protein Domains; CHO buňky; Models, Biological; Receptors, Muscarinic; N-methylskopolamin; Ligands; Protein Structure, Secondary; zvířata; Humans; Acceleration; Binding Sites; Cricetulus; vazba proteinů; Kinetics; biologické modely; simulace molekulární dynamiky; Cricetinae; mutantní proteiny; proteinové domény; vazebná místa; lidé; Animals